2013
DOI: 10.3389/fnana.2013.00011
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and connections of intratrigeminal cells and axons in the macaque monkey

Abstract: Trigeminal primary afferent fibers have small receptive fields and discrete submodalities, but second order trigeminal neurons often display larger receptive fields with complex, multimodal responses. Moreover, while most large caliber afferents terminate exclusively in the principal trigeminal nucleus, and pars caudalis (sVc) of the spinal trigeminal nucleus receives almost exclusively small caliber afferents, the characteristics of second order neurons do not always reflect this dichotomy. These surprising c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
(110 reference statements)
2
6
0
Order By: Relevance
“…They found that the injection reduced frequency and amplitude of spontaneous eye movement in both the treated and non-treated eyes and concluded that proprioceptive sensory signals from one eye are used to modulate movements of the other eye. This is consistent with the fact that the unilateral trigeminal inputs are distributed bilaterally by trigemino-trigeminal projections (Warren & May, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…They found that the injection reduced frequency and amplitude of spontaneous eye movement in both the treated and non-treated eyes and concluded that proprioceptive sensory signals from one eye are used to modulate movements of the other eye. This is consistent with the fact that the unilateral trigeminal inputs are distributed bilaterally by trigemino-trigeminal projections (Warren & May, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Rostral and caudal regions of the TBNC are connected through a dense longitudinal fiber system [206209]. Evidence that intersubnuclear pathways serve a “feed forward” facilitatory function has been reported in models for acute dental pain [210], headache [211] and evoked eye blinks [212]; however, a role in DED has not been determined.…”
Section: Neurobiological Features In Normal/non Dry Eye Diseasementioning
confidence: 99%
“…As this injection site included pV, and we have documented the presence of extensive intratrigeminal connection in the macaque (Warren & May, 2013), we tested whether the cells labeled in Case 1 might be trigeminotrigeminal neurons by injecting WGA‐HRP into pV (Case 2). Figure 3 shows the pattern of brainstem labeling in a case where the WGA‐HRP injection site involved pV, but did not involve VII (Figure 3a–c).…”
Section: Resultsmentioning
confidence: 99%